Correlation between Modified Tal Score and Oxygen Saturation Values Detected by Pulse Oximeter in Children with Bronchiolitis - Chakma, Kallins; Haque, Salina; Kumar Barua, Sanat; Das, Shuvra; Khisa, Uhtsa (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2026)
Background: A number of clinical scoring systems have been used for risk stratification of children with bronchiolitis, most of them have not validate in our setting. Modified Tal’s Score (MTS) is one of such clinical score. This study aimed to determine the relation between MTS and oxygen saturation (SpO2) measured by pulse Oximeterin children with acute bronchiolitis patients admitted to a tertiary-level hospital in Bangladesh. . Materials and methods: This cross-sectional study included 251 children aged <24 months with bronchiolitis from the department of pediatrics of Chittagong Medical College Hospital from April 2021 to March 2022. Severity was assessed by MTS and simultaneously SpO2 of patients were seen and recorded in a case record form. Correlation between MTS and SpO2 was assessed. Results: MTS showed a strong negative linear correlation with SpO2 (r = 0.82, 95% CI: -0.857 to -0.775). Linear regression analysis showed that 58.5% of the variation in SpO2 can be explained by the model containing only MTS. The mean (± SD) SpO2 value was 96.3±2.4% in children with a score of 2–5 (n=140), 90.65±5.6% in those with a score of 6–7 (n=48) and 86.6±4.7% in children with a score of 8 or more(n=63), (p < 0.001 by Bonferroni’s multiple comparison, when all two-way comparisons were done for each pair of results). With the cutoff value of 6, the MTS had 96.61% sensitivity, 71.88% specificity, and 98.57% negative predictive value to detect hypoxaemia. Conclusions: As modified TAL’s clinical scoring system strongly correlates with the SpO2, in absences of pulse oximetry MTS can be used to confirm severity of hypoxaemia in infants with bronchiolitis. Chatt Maa Shi Hosp Med Coll J; Vol.24 (1); Jan 2025; Page 3-7